Glucocorticoid treatment in early rheumatoid arthritis is independently associated with increased PCSK9 levels: data from a randomised controlled trial - Ronald F van Vollenhoven; Merete Lund Hetland; Till Uhlig; Dan Nordström; Jos WR Twisk; Mikkel Østergaard; Michael T Nurmohamed; Bjorn Gudbjornsson; Gerður Gröndal; Johan Frostegård; Kim Hørslev-Petersen; Anna Rudin; et al. (RMD Open)
Background Rheumatoid arthritis elevates cardiovascular disease risk. Proprotein convertase subtilisin/kexin type 9 (PCSK9), a regulator of low-density lipoprotein (LDL) metabolism, increases LDL-receptor breakdown in the liver, which elevates LDL-cholesterol levels. In addition, PCSK9 has direct effects on thrombogenesis and atherosclerotic plaque formation.We aimed to investigate (1) the impact of glucocorticoids and biological disease-modifying antirheumatic drug (bDMARD) treatments on PCSK9 and LDL-cholesterol levels, (2) whether this influence is different when autoantibodies are present and (3) the association between PCSK9 and LDL cholesterol.Methods In this post hoc analysis of the NORD-STAR trial, 296 newly diagnosed patients starting methotrexate with glucocorticoids, certolizumab pegol, abatacept or tocilizumab were included. Serum PCSK9 and LDL-cholesterol levels were measured at baseline and 24 weeks. Linear regression models were used to analyse the difference in PCSK9 and LDL cholesterol between glucocorticoid and bDMARD treatments at 24 weeks. In the second analysis, the interactions between the treatment groups and autoantibody status were added to the model.Results After 24 weeks, PCSK9 levels were higher in the glucocorticoid group than in the combined bDMARD treatment group (−276.0 (95% CI −468.2 to −83.9)). When compared with the bDMARD treatment, these increases were more pronounced in autoantibody-positive patients. Changes in LDL cholesterol exhibited a pattern distinct from PCSK9, as it increased in all treatments.Conclusion Glucocorticoid treatment was associated with increased PCSK9 levels after 24 weeks. When compared with the bDMARD treatments, these increases were more pronounced in rheumatoid factor, anticitrullinated protein antibody and antinuclear antibody-positive patients. Our data provide a potential mechanistic link between glucocorticoid treatment and cardiovascular disease.Funding Inger Bendix Foundation for Medical Research.Trial registration number EudraCT2011-004720-35, NCT01491815.